Cultural capital schemes in Asia: Mirroring Europe or carving out their own concepts? - OCON, David (Institutional Knowledge at Singapore Management University, 2017)
Despite bearing similar names and sharing certainaims, the implementation of the CulturalCity/Capital initiative in Europe and in the sub-regions of Southeast andNortheast Asia has been substantially dissimilar. In Europe, the annual EuropeanCity of Culture (ECOC) status commonly constitutes an opportunity toshowcase the best of the arts and culture of the host city, and counts on thesupport of sizable public funding. In Southeast Asia, the initiative scarcelyreceives any public or regional funds and the understanding of what thedesignation means varies widely from country to country. In Northeast Asia,regional diplomacy is one of the main motivations for initiating the scheme. This paper seeks to examinethe Cultural Capital patterns chosen in these Asian sub-regions in comparisonwith their European counterpart, as well as their motivations and reasons toexist. Ultimately, the paper investigates how much ASEAN and Northeast Asia aresimply trying to replicate the European model, carve their own concepts, or createhybrid schemes.